Impacto da suplementação materna com ácido linoleico conjugado sobre a maturação reflexa e função cognitiva da prole de ratos - Queiroz, Michelly Pires (2016)
The essential fatty acids are important lipids for formation of the central nervous system. During pregnancy and lactation the intake need is increased to further development of this system. The conjugated linoleic acid (CLA) is a fatty acid consisting of isomers of linoleic acid. The CLA is naturally produced by ruminant animals and is found in food products such as milk fat and meat of these animals. The CLA has been widely investigated because of its many beneficial health effects, however the effects of CLA on isolated CNS changes at this stage of life have not yet been investigated. This study aims to investigate the impact of maternal diet with different concentrations of CLA during pregnancy and lactation on the neonatal reflex maturation and cognitive function in rats. To this end, three groups were formed: the control group (GC) received a standard diet without added CLA; The GCLA1 group received the experimental diet containing 1% CLA and GCLA3 containing 3% CLA. After birth, the reflex responses were surveyed between 1 and 21 postnatal day, as well as the measurement of head size and body weight. At 42 days old, the animals participated in the habituation to the open field test, the second exposure occured after 7 days. For the evaluation of declarative memory, it was performed for object recognition test 3 days after the habituation test using the open field. After the test the animals were anesthetized and euthanized by cardiac puncture. The analyzes were compared by one way ANOVA test followed by the Holm Sidak test, considering significant difference for p <0.05. We used the Sigma start program for data analysis. The GCLA 1 and GCA3 showed acceleration in reflex maturation of puppies for most of the evaluated parameters. Body weight was higher compared to the control group (p <0.05). To assess the extent of the head, it can be seen that the GCLA1 and GCLA3 presented in laterolateral size measurements when compared to controls. In the anteroposterior extent GCLA1 and GCA3 shown to be lower when compared to the control group on day 1, with an increase in the perimeter evaluated in GCLA3 to compare it GCLA1 on the 7th and 21th day (p <0.05). On habituation in the open field test just wandered GCLA3 least the second open field indicating exposure to facilitating memory (p <0.05). In the long term object recognition test, a significant difference when comparing the time of exploration of familiar object to the time of operation of the new object occured in the GC, GCLA1 and GCLA3. Moreover, with respect to the explored ratio of the objects in GCLA1 there was a significant increase compared to GC and GCLA3 compared with GCLA1 (p <0.05). Maternal treatment with CLA anticipates reflex maturation, increases body weight, head size and improves responses in memory tests in the offspring of rats.